A Rapid Response Neural Network for Gear Box Diagnosis - 孟建; 蔡扬林; 屈梁生 (Jixie chuandong)
In this paper, an intelligent diagnostic system for gear box is developed, which is called, rapid response neural network. Its construction and fundamental function are discussed and a example is used to verify its effectiveness and practicability.